Traditional values and adolescent depression: Unraveling mediating mechanisms through self-esteem - Yayu Jia; Chen Zhang (PLoS ONE, 2025)
Drawing on nationally representative data from the 2018 China Family Panel Studies (CFPS), this research examines the mechanisms through which traditional values influence adolescent depressive symptoms via self-esteem. Utilizing Karlson-Holm-Breen (KHB) decomposition analysis with a sample of 4,217 adolescents aged 10−19 years, we found that overall traditional values demonstrated a nonsignificant total effect (β = −0.471, p = 0.116) yet exhibited a significant indirect effect through self-esteem (β = −0.447, p < 0.01 = 0.001, 95% CI [−0.716, −0.177]). Material-oriented and mortality-related values, including pursuit of wealth (β = 0.222, p = 0.178), avoiding social disapproval (β = −0.388, p = 0.031), and posthumous remembrance (β = −0.065, p = 0.648), demonstrated no significant mediation effects. Future-oriented traditional values manifested complete mediation through self-esteem, with significant indirect effects for intimate relations (β = −0.155, p = 0.026), achievement orientation (β = −0.226, p = 0.005), family cohesion (β = −0.255, p = 0.019), lineage continuation (β = −0.159, p = 0.020), and offspring success (β = −0.166, p = 0.042). Hedonic value orientation manifested partial mediation with both significant direct (β = −0.410, p = 0.050) and indirect effects (β = −0.312, p = 0.001). These findings illuminate how traditional values influence adolescent mental health in contemporary China, where distal life-course values operate through self-evaluative mechanisms, while proximate experiential values maintain direct psychological effects.